Analisis Perbandingan Metode Mobile-D Dan Prototype Pada Pembangunan Aplikasi E-Book Anak Usia Dini - Puji Rahayu; Nirmala Rahmi; Widya Wicaksana (JSINBIS (Jurnal Sistem Informasi Bisnis), 2022)
Literacy education in Indonesia is very low, which occupies the 62nd rank of 70 countries in the world. Based on the survey, one of the ways to increase the reading interest in the Indonesian people is to teach literacy education early in the age range of 3-6 years, where children begin to increase their cognitive, psychosocial and physical, and physical abilities. Therefore, we will develop an e-book as a learning medium to attract early childhood attention. The method used to develop this application is the Mobile-D method and prototype. The results of the test conducted on the E-Book Application of the Early Children's E-Book stated that all input forms and buttons in the system could run properly and the integrity of the output data on the input or the action carried out is following the user's expectations. The results of the analysis, design, implementation and comparison of the methods that have been carried out in the manufacture of this application show that the mobile-D development model is suitable for mobile development that can run on the system environment that accepts if there is a change or addition, the number of teams is a little, at level Applications, small-built systems and relatively short, development times. While the prototype development model is more suitable for systems made based on certain requests and needs by use.